An Early Islamic Inter-Settlement Agroecosystem in the Coastal Sand of the Yavneh Dunefield, Israel. (3rd October 2018) - Taxel, Itamar; Sivan, Dorit; Bookman, Revital; Roskin, Joel
ABSTRACT: This study examines the remains of an agricultural complex found in the Yavneh coastal dunefield, central Israel. Known as a plot-and-berm agroecosystem, the complex consisted of earthworks in a crisscross pattern of sand berms and sunken agricultural plots that were used for groundwater harvesting. The plots, which provided easy access to the high groundwater table and the berms around them, are overlaid by a gray sand unit covered by pottery sherds and artifacts. This gray sand is more fertile than the underlying sand, suggesting refuse enrichment. Artifactual similarity of the finds to those of inland (Tel) Yavneh suggests that Yavneh was the main source for the refuse additive. Based on artifacts and OSL ages it seems that this agroecosystem was active during the 10th to early 12th centuriesa.d . The agroecosystem demonstrates an early example of an Early Islamic agrotechnological attempt in marginal and sandy regions of the Mediterranean basin.